Anal Sphincter Function After Hemorrhoidectomy - A. M. Kuzminov; O. Yu. Fomenko; I. A. Mukhin; S. A. Frolov; D. V. Vyshegorodtsev; V. Yu. Korolik; S. T. Minbaev; S. V. Belousova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To generalize and present current data on the development of approaches to hemorrhoidectomy, as well as to analyse the function of the rectal closing apparatus after surgery.Key findings. The haemorrhoid disease is one of the most common human diseases and the most common reason for visiting a coloproctologist. In Russia, the prevalence of haemorrhoids amounts to 130–145 people per 1,000 adult population, with its proportion in the structure of colon diseases varying from 34 to 41 %. Minimally invasive methods for treating such conditions have been shown to be effective in patients with 1–3 stage haemorrhoids. However, these methods have shown little value at stage 4 hemorrhoids, largely because they fail to affect all parts of the disease pathogenesis. Thus, hemorrhoidectomy remains to be the “gold standard” for stage 4 hemorrhoids treatment, which is aimed at eliminating the three main vascular collectors. Hemorrhoidectomy is accompanied by the risk of stricture and postoperative anal sphincter failure. In this regard, it is necessary to assess the functional state of the rectal closing apparatus after hemorrhoidectomy. Improving hemorrhoidectomy, for example, by the use of an ultrasonic scalpel, allows the hemorrhoidectomy to be performed without additional sewing of vessels and coagulation, and the injury of the anal sphincter to be minimized.Conclusion. The possibility of injuring the anal sphincter is a serious problem in anal surgery. Anal sphincter incontinence is a serious illness that exacerbates the patients’ social life. Unfortunately, the issue of anal sphincter incontinence after hemorrhoidectomy is under-investigated, resulting in few rehabilitation programs.